A highly dispersed ruthenium-platinum bimetallic catalyst and its preparation method and application
By spraying the microemulsion containing Ru and Pt salts on the R-P type lanthanum aluminum oxide support, a high-dispersed ruthenium platinum bimetallic catalyst was prepared, which solved the problems of low starting efficiency and short life of existing catalysts at room temperature, and achieved rapid start-up and long-life pulse application of HAN liquid propellant.
Patent Information
- Application Number
- CN202411813630.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-11
AI Technical Summary
Existing catalysts are difficult to quickly start at room temperature and meet the long-life application requirements of HAN liquid propellant for tens of thousands of pulses.
Using R-P type lanthanum aluminum oxide as a support, a microemulsion containing soluble Ru and Pt salts was sprayed onto the support, and after freeze-drying and calcining in an inert atmosphere, a highly dispersed ruthenium platinum bimetallic catalyst was prepared, and the particle sizes of the active components Ru and Pt were 1.0~2.5 nm.
It realizes the rapid start of HAN liquid propellant at room temperature and meets the long-life application requirements of tens of thousands of pulse starts. The catalyst has a high active metal load, small particle size, and has high activity.
Smart Images

Figure CN119281326B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a preparation method and application of a highly dispersed ruthenium-platinum bimetallic catalyst. The present invention uses RP-type lanthanum aluminum oxide as a carrier, sprays a microemulsion containing soluble Ru and Pt salts onto the carrier, and obtains a catalyst in which active metals Ru and Pt are dispersed between lanthanum aluminum oxide layers and on the surface after freeze drying and inert atmosphere roasting. The active component Ru accounts for 10-25wt% of the carrier mass, and Pt accounts for 5-20wt% of the carrier mass. The size of the active component metal particles is 1.0-2.5nm. The catalyst can quickly start hydroxylamine nitrate (HAN) liquid propellant at room temperature and meet the long-life application requirements of tens of thousands of pulse starts of HAN propellant. Background Art
[0002] Liquid propellants have the advantages of high specific impulse, easy thrust adjustment, and multiple pulse ignition. They are widely used in various tactics, large launch vehicles, and spacecraft attitude and orbit control systems. To date, liquid propellants are still the most widely used propellants in launch vehicles, space vehicles, and weapon power systems in various countries. Since the 1960s, hydrazine has been the dominant standard monopropellant in aerospace applications.
[0003] With the continuous development of aerospace technology and the requirements for environmental protection and launch costs, finding cheap, non-toxic, pollution-free and green propellants has become a goal pursued in the aerospace field.
[0004] Compared with anhydrous hydrazine, hydroxylamine nitrate (HAN) liquid propellant is non-toxic and non-polluting, and has the advantages of high density, high specific impulse, low freezing point, and stable safety performance. When used in propulsion power systems, it has the advantages of high propulsion efficiency and strong environmental adaptability. It is one of the new generation of monopropellant technologies that are currently being developed at home and abroad.
[0005] Catalyst technology is one of the core technologies of HAN liquid propulsion technology. It plays a key role in converting the chemical energy of HAN liquid propellant into kinetic energy. The performance of the catalyst is crucial to whether HAN liquid propellant can be completely decomposed and even the size of the kinetic energy output. HAN liquid propellant itself has the characteristics of good safety, high performance, high stability, etc. It is difficult to be catalytically decomposed, so the catalytic activity of HAN catalyst is extremely high.
[0006] Ruthenium-platinum bimetallic catalysts have the advantages of low catalytic reaction temperature, good activity and selectivity, fast reaction speed and a wide range of permissible operating space velocity, and have a wide range of uses.
[0007] RP-type oxides (A2BO4) have a layered structure and a variety of components. They can adjust various metal ions and stabilize some uncommon or mixed-valence active ions. They have a good dispersing effect on the loaded active metals and are one of the suitable carriers for preparing ultrafine nanocatalysts with high stability and high dispersion.
[0008] The present invention uses RP-type lanthanum aluminum oxide as a carrier, sprays a microemulsion containing soluble Ru and Pt salts onto the carrier, anchors the active components Ru and Pt on the carrier, and there is a strong interaction between the active metal and the carrier, which can effectively inhibit the volatilization of the active metal components, thereby preparing a highly dispersed ruthenium-platinum bimetallic catalyst. At present, there is no report on the high-load small particles prepared by this method and their use in the decomposition of HAN liquid propellant, rapid start-up at room temperature, and the completion of tens of thousands of pulse starts of HAN propellants. Summary of the invention
[0009] The present invention relates to the preparation and application of a highly dispersed ruthenium-platinum bimetallic catalyst. The catalyst can start HAN propellant at room temperature, meeting the practical application requirements of HAN propellant.
[0010] To achieve the above object, the technical solution adopted by the present invention is:
[0011] A highly dispersed ruthenium-platinum bimetallic catalyst, comprising a carrier and active components Ru and Pt; the active component Ru accounts for 10-25wt% (preferably 12-22wt%, more preferably 15-20wt%) of the carrier mass, Pt accounts for 5-20wt% (preferably 8-18wt%, more preferably 10-15wt%) of the carrier mass, and the active component metal particle size is 1.0-2.5nm.
[0012] The catalyst carrier is RP type lanthanum aluminum oxide.
[0013] The catalyst carrier is prepared by a hydrothermal method, and the steps are as follows:
[0014] First, at a molar ratio of La:Al=1:2~3:1 (preferably 1:1~2:1), nitrate containing La and Al is dissolved in deionized water to prepare solution A, wherein the mass content of La nitrate is 2.5~6wt% (preferably 3~6wt%, more preferably 3.5~5.5wt%); sodium hydroxide and sodium carbonate are dissolved in deionized water at a molar ratio of 2:3~3.5:1 (preferably 1:1~2:1) to prepare solution B, wherein the molar ratio of sodium hydroxide to the sum of metal La and Al salts is 3:1~6:1 (preferably 4:1~5:1); after mixing solutions A and B evenly, transfer them to a closed reactor, react at 100~120°C for 10~20h, cool naturally to room temperature, wash and filter, dry at 80~100°C for 10~20h, and calcine in air at 800~900°C for 4~8h to prepare RP type lanthanum aluminum oxide.
[0015] The method for preparing the catalyst comprises the following steps:
[0016] 1) First, a microemulsion containing Ru and Pt is prepared, and an active metal Ru precursor and a chloroplatinic acid aqueous solution, hexadecyltrimethylammonium bromide (CTAB) and n-hexane are prepared in a mass ratio of 1.6-2.5:2.7-3.6:4.5-5.5 (preferably 1.8-2.1:2.9-3.2:4.8-5.2) to prepare a microemulsion solution containing active metals Ru and Pt, wherein the mass content of the active metal Ru precursor in the solution is 2.5-7wt% (preferably 3-5.5wt%, more preferably 3.5-5wt%), and the mass content of chloroplatinic acid is 1-5wt% (preferably 2-4.5, more preferably 2.5-4wt%);
[0017] 2) Spraying a microemulsion solution of a soluble salt of active metal Ru with a content of 1.0-2.5wt% (preferably 1.5-2.0wt%) relative to the carrier and 0.5-2.0wt% (preferably 1.0-1.5wt%) of chloroplatinic acid with a content of 0.5-2.0wt% (preferably 1.0-1.5wt%) relative to the carrier onto lanthanum aluminum oxide, leaving it to stand for 1-2 hours, freeze-drying it at a low temperature of -25--15°C (preferably -20--18°C) for 8-12 hours, and then calcining it at 300-400°C for 2-4 hours in an inert atmosphere to obtain a catalyst in which active metals Ru and Pt are dispersed between the layers and on the surface of the lanthanum aluminum oxide;
[0018] 3) Repeat steps 1) and 2) 8-10 times, for a total of 9-11 times.
[0019] The soluble salt of the active metal Ru is one or both of ruthenium acetate and ruthenium trichloride solution.
[0020] The highly dispersed ruthenium-platinum bimetallic catalyst is used for catalyzing the decomposition of HAN propellant.
[0021] The highly dispersed ruthenium-platinum bimetallic catalyst is used to catalyze the rapid start-up and decomposition of HAN propellant at room temperature, meeting the long-life application requirements of HAN propellant with tens of thousands of pulse starts.
[0022] The catalyst needs to be activated before the catalytic reaction, and the pretreatment conditions are: reduction at 400-600° C. for 2-4 hours in a hydrogen atmosphere.
[0023] The present invention has the following advantages:
[0024] 1) Compared with the prior art, the catalyst carrier of the present invention is RP-type lanthanum aluminum oxide. The RP-type oxide has a layered structure and a variety of components. It can adjust various metal ions and stabilize some uncommon or mixed-valence active ions. The RP-type oxide has highly active lattice oxygen, which is beneficial to high-temperature catalytic reactions;
[0025] 2) Compared with the prior art, the technical solution of the present invention first prepares a high specific surface area RP-type lanthanum aluminum oxide, and prepares the active metal Ru and Pt precursor solutions into a microemulsion, and then fixes the active metals Ru and Pt between the layers and on the surface of the lanthanum aluminum oxide with a two-dimensional layered structure;
[0026] 3) Compared with the prior art, the ruthenium-platinum bimetallic catalyst prepared by the technical solution of the present invention has a higher active metal loading and a smaller particle size of about 1.0-2.5 nm, and has a higher activity. It can quickly start the HAN liquid propellant at room temperature and meet the long-life application requirements of HAN liquid propellant for tens of thousands of pulse starts. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is an electron microscope photograph of the Ru15Pt15 / La-Al-RP-H1 catalyst obtained in Example 3.
[0028] Figure 2 This is an electron microscope photograph of the Ru10Pt20 / La-Al-RP-H1 catalyst obtained in Example 5.
[0029] Figure 3 This is an electron microscope photograph of the Ru25Pt5 / La-Al-RP-H1 catalyst obtained in Example 6.
[0030] Figure 4 This is an electron microscope photograph of the Ru / La-Al-RP catalyst obtained in Comparative Example 6.
[0031] Figure 5 This is the room temperature pulse ignition test result of the liquid HAN engine of the Ru15Pt15 / La-Al-RP-H1 catalyst obtained in Example 3 (Example 13).
[0032] Figure 6 This is the 250th 40 pulse ignition test result of the liquid HAN engine using the Ru15Pt15 / La-Al-RP-H1 catalyst obtained in Example 3 (Example 13).
[0033] Figure 7 This is the room temperature pulse ignition test result of the liquid HAN engine of the Ru25Pt5 / La-Al-RP-H1 catalyst obtained in Example 6 (Example 16).
[0034] Figure 8 This is the 250th 40 pulse ignition test result of the liquid HAN engine using the Ru25Pt5 / La-Al-RP-H1 catalyst obtained in Example 6 (Example 16).
[0035] Fig. 9 This is the room temperature pulse ignition test result of the liquid HAN engine using the Ru25 / La-Al-RP-H1 catalyst obtained in Comparative Example 6 (Example 26).
[0036] Fig.10 This is the room temperature pulse ignition test result of the liquid HAN engine using the Ru25 / La-Al-RP-H1 catalyst obtained in Comparative Example 6 (Example 26). DETAILED DESCRIPTION
[0037] Example 1 Preparation of RP-type lanthanum aluminum oxide carrier by hydrothermal method
[0038] First, 6.44 g of lanthanum nitrate and 3.75 g of aluminum nitrate nonahydrate were dissolved in 100 mL of deionized water to prepare solution A. 6 g of sodium hydroxide and 15.9 g of sodium carbonate were weighed and dissolved in 100 mL of water to prepare solution B. After solutions A and B were mixed evenly, they were transferred to a 500 mL pressure reactor lined with polytetrafluoroethylene. The reactor was placed in a constant temperature electric heating blast drying oven at 100 ° C for 20 h, cooled naturally to room temperature, washed and filtered, and then heated at 100 ° C for 20 h. o C oven for 10 h and calcined in air at 800 °C for 8 h to obtain lanthanum aluminum oxide, recorded as La-Al-RP-H1. XRD results showed obvious characteristic peaks at 31.9°, 33.7°, 24.7°, and 44.5°, which was attributed to RP-type lanthanum aluminum oxide. The specific surface area results are shown in Table 1. From the scanning electron microscopy results, it can be seen that the carrier has a layered structure with an interlayer spacing of 5~8nm.
[0039] Example 2
[0040] The process and conditions are the same as those in Example 1, except that first, 3.22 g of 50 wt% lanthanum nitrate aqueous solution and 3.75 g of aluminum nitrate nonahydrate are dissolved in 100 mL of deionized water to obtain solution A; 3 g of sodium hydroxide and 15.9 g of sodium carbonate are weighed and dissolved in 100 mL of water to obtain solution B; solutions A and B are mixed evenly and then transferred to a 500 mL pressure reactor lined with polytetrafluoroethylene, and the reactor is placed in a constant temperature electric heating blast drying oven at 120° C. for 10 h, cooled naturally to room temperature, washed and filtered, and then dried in an oven at 80° C. for 20 h, and calcined at 900 °C in air for 4 h to obtain lanthanum aluminum oxide, recorded as La-Al-RP-H2. XRD results showed obvious characteristic peaks at 31.9°, 33.7°, 24.7°, and 44.5°, which was classified as RP-type lanthanum aluminum oxide. The specific surface area results are shown in Table 1. From the scanning electron microscopy results, it can be seen that the carrier has a layered structure with an interlayer spacing of 5~8nm.
[0041] Comparative Example 1 Preparation of RP-type lanthanum aluminum oxide by coprecipitation method
[0042] The process and conditions are the same as those in Example 1, except that first, 6.44 g of 50 wt% manganese nitrate aqueous solution and 3.75 g of aluminum nitrate nonahydrate are dissolved in 100 mL of deionized water to obtain solution A; 6 g of sodium hydroxide and 15.9 g of sodium carbonate are weighed and dissolved in 100 mL of water to obtain solution B; solutions A and B are placed in constant pressure funnels to control the flow rate (1 drop per second) and dripped into a beaker, and the pH is controlled at 9.5-10 during the process. After the titration, stirring is continued for 30 min to obtain a precipitate, which is placed in a 60°C oven for 20 h, cooled naturally to room temperature, washed and filtered, dried in a 100°C oven for 10 h, and calcined in air at 800°C for 8 h Lanthanum aluminum oxide, La-Al-RP-C, was obtained. XRD results showed obvious characteristic peaks at 31.9°, 33.7°, 24.7°, and 44.5°, which was classified as RP-type lanthanum aluminum oxide. The specific surface area results are shown in Table 1. From the scanning electron microscopy results, it can be seen that the carrier has a layered structure with an interlayer spacing of 12~18nm.
[0043] Comparative Example 2 Preparation of RP-type lanthanum aluminum oxide by urea precipitation method
[0044] The process and conditions are the same as those of Example 1, except that first, 6.44 g of 50 wt% manganese nitrate aqueous solution and 3.75 g of aluminum nitrate nonahydrate are dissolved in 100 mL of deionized water to prepare solution A; 12 g of urea is weighed in 100 mL of water to prepare solution B; after mixing solutions A and B evenly, the mixture is placed in an oil bath at 102° C. for 10 h, cooled naturally to room temperature, washed, filtered, and then heated at 100° C. oC oven for 10 h and calcined in air at 800 ° C for 8 h to obtain lanthanum aluminum oxide, La-Al-RP-N. XRD results showed that there were obvious characteristic peaks at 31.9°, 33.7°, 24.7°, and 44.5°, which were attributed to RP-type lanthanum aluminum oxide. The specific surface area results are shown in Table 1. From the scanning electron microscopy results, it can be seen that the carrier has a layered structure with an interlayer spacing of 10~15nm.
[0045] Table 1 Specific surface area results of different catalysts
[0046] Example Preparation method <![CDATA[Specific surface area / m 2 g -1 > Example 1 Hydrothermal method 123 Example 2 Hydrothermal method 116 Comparative Example 1 Coprecipitation 61 Comparative Example 2 Urea precipitation method 76
[0047] Example 3
[0048] 1) First, 2 g of an aqueous solution containing 0.42 g of ruthenium acetate and 0.40 g of chloroplatinic acid hexahydrate, 3 g of CTAB and 5 g of cyclohexane are prepared into a microemulsion containing 4.2 wt % of ruthenium acetate and 4.0 wt % of chloroplatinic acid hexahydrate;
[0049] 2) The microemulsion solution prepared in step 1) (a microemulsion containing 1.5 wt% of active metal Ru and 1.5 wt% of soluble salt of active metal Pt relative to the carrier) was sprayed onto 10 g of lanthanum aluminum oxide La-Al-RP-H1 prepared in Example 1, allowed to stand for 1.5 h, and then freeze-dried at a low temperature of -15°C for 12 h.
[0050] The sample was then placed in a calcination tube and calcined at 300°C for 4 hours in an argon atmosphere to obtain a catalyst in which active metals Ru and Pt were dispersed between the lanthanum aluminum oxide layers and on the surface.
[0051] 3) Repeat steps 1) and 2) in accordance with the above process and conditions. After the process is repeated 9 times (a total of 10 times), switch the argon gas to hydrogen, raise the temperature to 500 ° C, and reduce for 3 hours to obtain a catalyst with a Ru content of 30wt% relative to the carrier and a Pt content of 1.2wt% relative to the carrier, which is recorded as Ru15Pt15 / La-Al-RP-H1. The electron microscopy results are shown in Figure 1 ,It can be seen from the figure that the metal particles (Ru and Pt) of the active components on the carrier surface are evenly distributed, and the particle size is 1.0~2.3nm.
[0052] Example 4
[0053] The process and conditions are the same as those in Example 3, except that the carrier in step 2) is the lanthanum aluminum oxide La-Al-RP-H2 prepared in Example 2, and the amounts of other materials and operating conditions are the same as those in Example 3. A catalyst with a Ru content of 15 wt% and a Pt content of 15 wt% relative to the carrier is obtained, recorded as Ru15Pt15 / La-Al-RP-H2. It can be seen from the electron microscopy results that the metal particles of the active component are evenly distributed and have a size of 1.1~2.5 nm.
[0054] Example 5
[0055] The process and conditions are the same as those of Example 3, except that in step 1), 2 g of an aqueous solution containing 0.69 g of ruthenium acetate and 0.14 g of chloroplatinic acid hexahydrate, 3 g of CTAB and 5 g of cyclohexane are first prepared into a microemulsion containing 6.9 wt % of ruthenium acetate and 1.4 wt % of chloroplatinic acid hexahydrate;
[0056] According to the above process and conditions, steps 1) and 2) were repeated 9 times (a total of 10 times), and then the argon gas was switched to hydrogen, the temperature was raised to 400°C, and the reduction was carried out for 4 hours. The other material amounts and operating conditions were the same as those in Example 3, and a catalyst containing 25wt% Ru and 1wt% Pt relative to the carrier was obtained, which was recorded as Ru25Pt5 / La-Al-RP-H1. The electron microscopy results are shown in Figure 2 ,It can be seen from the figure that the active component metal particles are ,evenly distributed and have a size of 1.0~2.4nm.
[0057] Example 6
[0058] The process and conditions are the same as those of Example 3, except that in step 1), 2 g of an aqueous solution containing 0.28 g of ruthenium acetate and 0.53 g of chloroplatinic acid hexahydrate, 3 g of CTAB and 5 g of cyclohexane are first prepared into a microemulsion containing 2.8 wt % of ruthenium acetate and 5.3 wt % of chloroplatinic acid hexahydrate;
[0059] According to the above process and conditions, steps 1) and 2) were repeated 9 times (a total of 10 times), and then the argon gas was switched to hydrogen, the temperature was raised to 600°C, and the reduction was carried out for 2 hours. The other material amounts and operating conditions were the same as those in Example 3. The other material amounts and operating conditions were the same as those in Example 3 to obtain a catalyst with a Ru content of 10wt% and a Pt content of 20wt% relative to the carrier, recorded as Ru10Pt20 / La-Al-RP-H1, and the electron microscopy results are shown in Figure 3 ,It can be seen from the figure that the active component metal particles are ,evenly distributed and have a size of 1.0~2.5nm.
[0060] Example 7
[0061] The process and conditions are the same as those in Example 3, except that ruthenium trichloride trihydrate is used instead of ruthenium acetate in step 1), and the catalyst is freeze-dried at -25°C for 8 h in step 2). The amounts of other materials and the operating conditions are the same as those in Example 3, and a catalyst containing 15 wt% Ru and 15 wt% Pt relative to the carrier is obtained, which is recorded as Ru15Pt15 / La-Al-RP-H3. As can be seen from the electron microscopy results, the metal particles of the active component are evenly distributed and have a size of 1.3~2.5 nm.
[0062] Example 8
[0063] The process and conditions are the same as those in Example 3, except that in step 1), 2 g of an aqueous solution containing 0.33 g of ruthenium acetate and 0.48 g of chloroplatinic acid hexahydrate, 3 g of CTAB and 5 g of cyclohexane are first prepared into a microemulsion containing 3.3 wt% of ruthenium acetate and 4.8 wt% of chloroplatinic acid hexahydrate; the microemulsion solution prepared in step 1) is sprayed onto 10 g of lanthanum aluminum oxide La-Al-RP-H1 prepared in Example 1, and the other material amounts and operating conditions are the same as those in Example 3, to obtain a catalyst containing 12 wt% of Ru and 18 wt% of Pt relative to the carrier, recorded as Ru12Pt18 / La-Al-RP-H1. It can be seen from the electron microscopy results that the metal particles of the active component are evenly distributed and have a size of 1.0~2.3 nm.
[0064] Example 9
[0065] The process and conditions are the same as those in Example 3, except that in step 1), 2 g of an aqueous solution containing 0.50 g of ruthenium acetate and 0.32 g of chloroplatinic acid hexahydrate, 3 g of CTAB and 5 g of cyclohexane are first prepared into a microemulsion containing 5.0 wt% of ruthenium acetate and 3.2 wt% of chloroplatinic acid hexahydrate; the microemulsion solution prepared in step 1) is sprayed onto 10 g of lanthanum aluminum oxide La-Al-RP-H1 prepared in Example 1, and the other material amounts and operating conditions are the same as those in Example 3, to obtain a catalyst containing 18 wt% of Ru and 12 wt% of Pt relative to the carrier, recorded as Ru18Pt12 / La-Al-RP-H1. It can be seen from the electron microscopy results that the metal particles of the active component are evenly distributed and have a size of 1.1~2.4 nm.
[0066] Example 10
[0067] The process and conditions are the same as those in Example 3, except that in step 1), 2 g of an aqueous solution containing 0.61 g of ruthenium acetate and 0.21 g of chloroplatinic acid hexahydrate, 3 g of CTAB and 5 g of cyclohexane are first prepared into a microemulsion containing 6.1 wt% of ruthenium acetate and 2.1 wt% of chloroplatinic acid hexahydrate; the microemulsion solution prepared in step 1) is sprayed onto 10 g of lanthanum aluminum oxide La-Al-RP-H1 prepared in Example 1, and the other material amounts and operating conditions are the same as those in Example 3, to obtain a catalyst having a Ru content of 22 wt% and a Pt content of 8 wt% relative to the carrier, recorded as Ru22Pt8 / La-Al-RP-H1. It can be seen from the electron microscopy results that the metal particles of the active component are evenly distributed and have a size of 1.2~2.5 nm.
[0068] Embodiment 11
[0069] The process and conditions are the same as those in Example 3, except that in step 1), 2 g of an aqueous solution containing 0.69 g of ruthenium acetate and 0.27 g of chloroplatinic acid hexahydrate, 3 g of CTAB and 5 g of cyclohexane are first prepared into a microemulsion containing 6.9 wt % of ruthenium acetate and 2.7 wt % of chloroplatinic acid hexahydrate; the microemulsion solution prepared in step 1) is sprayed onto 10 g of lanthanum aluminum oxide La-Al-RP-H1 prepared in Example 1, and the other material amounts and operating conditions are the same as those in Example 3, to obtain a catalyst containing 25 wt % of Ru and 10 wt % of Pt relative to the carrier, recorded as Ru25Pt10 / La-Al-RP-H1. It can be seen from the electron microscopy results that the metal particles of the active component are evenly distributed and have a size of 1.3~2.4 nm.
[0070] Example 12
[0071] The process and conditions are the same as those in Example 3, except that in step 1), 2 g of an aqueous solution containing 0.55 g of ruthenium acetate and 0.40 g of chloroplatinic acid hexahydrate, 3 g of CTAB and 5 g of cyclohexane are first prepared into a microemulsion containing 5.5 wt% of ruthenium acetate and 4.0 wt% of chloroplatinic acid hexahydrate; the microemulsion solution prepared in step 1) is sprayed onto 10 g of lanthanum aluminum oxide prepared in Example 1, and the amounts of other materials and operating conditions are the same as those in Example 3, to obtain a catalyst containing 25 wt% of Ru and 10 wt% of Pt relative to the carrier, recorded as Ru20Pt15 / La-Al-RP-H1. It can be seen from the electron microscopy results that the metal particles of the active component are evenly distributed and have a size of 1.1~2.5 nm.
[0072] Comparative Example 3
[0073] The process and conditions are the same as those in Example 3, except that the carrier used in step 2) is the lanthanum aluminum oxide La-Al-RP-C prepared in Comparative Example 1, and the amounts of other materials and operating conditions are the same as those in Example 3. A catalyst with a Ru content of 15 wt% and a Pt content of 15 wt% relative to the carrier is obtained, which is recorded as Ru15Pt15 / La-Al-RP-C. It can be seen from the electron microscopy results that the active metal particles are of different sizes, with a wide particle size distribution range, and the size is between 7 and 50 nm.
[0074] Comparative Example 4
[0075] The process and conditions are the same as those in Example 3, except that the carrier used in step 2) is the lanthanum aluminum oxide La-Al-RP-N prepared in Comparative Example 2, and the amounts of other materials and operating conditions are the same as those in Example 3. A catalyst with a Ru content of 15 wt% and a Pt content of 15 wt% relative to the carrier is obtained, which is recorded as Ru15Pt15 / La-Al-RP-N. It can be seen from the electron microscopy results that the active metal particles are of different sizes, with a wide particle size distribution range, and a size between 5 and 40 nm.
[0076] Comparative Example 5
[0077] The process and conditions are the same as those in Example 3, except that in step 2), the microemulsion solution prepared in step 1) is impregnated onto 10 g of lanthanum aluminum oxide prepared in Example 1 by an impregnation method. The amounts of other materials and the operating conditions are the same as those in Example 3, and a catalyst having a Ru content of 15 wt% and a Pt content of 15 wt% relative to the carrier is obtained, which is recorded as Ru15Pt15(imp) / La-Al-RP-H1. The active metal particles are of different sizes, with a wide particle size range distribution, and a size between 5 and 50 nm.
[0078] Comparative Example 6
[0079] The process and conditions are the same as those in Example 3, except that 1) 2 g of an aqueous solution containing 0.69 g of ruthenium acetate, 3 g of CTAB and 5 g of cyclohexane are first prepared into a microemulsion containing 6.9 wt % of ruthenium acetate; 2) the microemulsion solution prepared in step 1) (a microemulsion of a soluble salt of active metal Ru with respect to the carrier content of 2.5 wt %) is sprayed onto 10 g of lanthanum aluminum oxide, allowed to stand for 1.5 h, and then freeze-dried at a low temperature of -15°C for 12 h to obtain a hydrotalcite loaded with Ru on the surface; 3) after repeating steps 1) and 2) above 10 times, the argon gas is switched to hydrogen, the temperature is raised to 400°C, and the catalyst is reduced for 4 hours to obtain a catalyst containing only Ru, which is recorded as Ru25 / La-Al-RP-H1, and its electron microscopy results are shown in Figure 4,As can be seen from the figure, the Ru particles are of different sizes, with a wide range of sizes ranging from 2.5 to 20 nm.
[0080] Comparative Example 7
[0081] The process and conditions are the same as those in Example 3, except that 1) 2 g of an aqueous solution containing 0.53 g of chloroplatinic acid hexahydrate, 3 g of CTAB and 5 g of cyclohexane are first prepared into a microemulsion containing 5.3 wt% of chloroplatinic acid; 2) the microemulsion solution prepared in step 1) (a microemulsion containing 2.0 wt% of an active metal Pt soluble salt relative to the carrier) is sprayed onto 10 g of lanthanum aluminum oxide, allowed to stand for 1.5 h, and then freeze-dried at a low temperature of -15°C for 12 h; the other material amounts and operating conditions are the same as those in Example 5, and a catalyst containing 20 wt% of Pt relative to the carrier is obtained, recorded as Pt20 / La-Al-RP-H1. It can be seen from the electron microscopy results that the metal particles of the active component are unevenly distributed, and the particle size range is relatively wide, with a size of 5 to 20 nm.
[0082] Comparative Example 8
[0083] The process and conditions are the same as those in Example 3, except that in step 1), 2 g of an aqueous solution containing 0.83 g of ruthenium acetate and 0.13 g of chloroplatinic acid hexahydrate, 3 g of CTAB and 5 g of cyclohexane are first prepared into a microemulsion containing 8.3 wt% of ruthenium acetate and 1.3 wt% of chloroplatinic acid hexahydrate; the microemulsion solution prepared in step 1) is sprayed onto 10 g of lanthanum aluminum oxide prepared in Example 1, and the amounts of other materials and operating conditions are the same as those in Example 3, to obtain a catalyst having a Ru content of 30 wt% and a Pt content of 5 wt% relative to the carrier, recorded as Ru30Pt5 / La-Al-RP-H1. It can be seen from the electron microscopy results that the metal particles of the active component are evenly distributed, with a wide particle size range of 3 to 10 nm.
[0084] Comparative Example 9
[0085] The process and conditions are the same as those in Example 3, except that in step 1), 2 g of an aqueous solution containing 0.28 g of ruthenium acetate and 0.66 g of chloroplatinic acid hexahydrate, 3 g of CTAB and 5 g of cyclohexane are first prepared into a microemulsion containing 2.8 wt% of ruthenium acetate and 6.6 wt% of chloroplatinic acid hexahydrate; the microemulsion solution prepared in step 1) is sprayed onto 10 g of lanthanum aluminum oxide prepared in Example 1, and the amounts of other materials and operating conditions are the same as those in Example 3, to obtain a catalyst containing 10 wt% of Ru and 25 wt% of Pt relative to the carrier, recorded as Ru10Pt25 / La-Al-RP-H1. It can be seen from the electron microscopy results that the metal particles of the active component are evenly distributed, with a wide particle size range of 6 to 17 nm.
[0086] Embodiment 13
[0087] 1.8g of Ru15Pt15 / La-Al-RP-H1 catalyst prepared in Example 3 was loaded into the HAN liquid engine catalyst bed, and HAN liquid propellant was supplied by gas extrusion and solenoid valve control. The flow rate of the propellant was 3.6g / s. The propellant was pulsed and ignited at room temperature. Nine pulse tests were completed. Immediately after the test, 10,000 pulses (40 pulses each time, divided into 250 times) were performed to evaluate the performance of the catalyst by measuring the temperature of the engine catalyst bed and the pressure of the combustion chamber. The results of the pulse test at room temperature are shown in Figure 5 , Figure 6 The results of the 250th 40 pulse tests are shown in Figure 1. The curve marked with T is the temperature of the engine catalyst bed, and the curve marked with Pc is the pressure of the engine combustion chamber. It can be seen from the figure that the HAN liquid propellant undergoes catalytic decomposition at room temperature and completes 10,000 pulse test conditions. The catalyst bed temperature rises from room temperature to 285°C, and the chamber pressure stabilizes between 0.81-0.86MPa. The pulse test results show that the catalyst has good performance.
[0088] Embodiment 14
[0089] The process and conditions are the same as those in Example 13. The difference from Example 13 is that the Ru15Pt15 / La-Al-RP-H2 catalyst prepared in Example 4 is loaded into the HAN liquid engine catalyst bed. The other material amounts and operating conditions are the same as those in Example 13. From the test results, it can be seen that the HAN liquid propellant undergoes catalytic decomposition at room temperature. After 10,000 pulse tests, the catalyst bed temperature rises, the chamber pressure stabilizes between 0.80-0.86 MPa, and the catalyst performance is good.
[0090] Embodiment 15
[0091] The process and conditions are the same as those of Example 13. The difference from Example 13 is that the Ru25Pt5 / La-Al-RP-H1 catalyst prepared in Example 5 is loaded into the HAN liquid engine catalyst bed. The other material amounts and operating conditions are the same as those of Example 13. From the test results, it can be seen that the HAN liquid propellant undergoes catalytic decomposition at room temperature. After 10,000 pulse tests, the catalyst bed temperature rises from room temperature to 270°C, the chamber pressure is stabilized between 0.81-0.86 MPa, and the catalyst performance is good.
[0092] Example 16
[0093] The process and conditions are the same as those of Example 13. The difference from Example 13 is that the Ru10P20 / La-Al-RP-H1 catalyst prepared in Example 6 is loaded into the HAN liquid engine catalyst bed. The other material amounts and operating conditions are the same as those of Example 13. The pulse test results at room temperature are shown in FIG. Figure 7 The results of the 250th 40-pulse test are shown in Figure 8 ,It can be seen from the figure that HAN liquid propellant undergoes catalytic decomposition at room temperature. After completing 10,000 pulse tests, the catalyst bed temperature rises from room temperature to 268°C, and the chamber pressure stabilizes between 0.81-0.87MPa. The catalyst performance is good.
[0094] Embodiment 17
[0095] The process and conditions are the same as those of Example 13. The difference from Example 13 is that the Ru15Pt15 / La-Al-RP-H3 catalyst prepared in Example 7 is loaded into the catalyst bed of the HAN liquid engine. The amounts of other materials and the operating conditions are the same as those of Example 13. From the test results, it can be seen that the HAN liquid propellant undergoes catalytic decomposition at room temperature. After 10,000 pulse tests, the catalyst bed temperature rises from room temperature to 272°C, the chamber pressure is stabilized between 0.81-0.87 MPa, and the catalyst performance is good.
[0096] Embodiment 18
[0097] The process and conditions are the same as those of Example 13. The difference from Example 13 is that the Ru12Pt18 / La-Al-RP-H1 catalyst prepared in Example 8 is loaded into the catalyst bed of the HAN liquid engine. The amounts of other materials and the operating conditions are the same as those of Example 13. From the test results, it can be seen that the HAN liquid propellant undergoes catalytic decomposition at room temperature. After 10,000 pulse tests, the catalyst bed temperature rises from room temperature to 262° C., the chamber pressure is stabilized between 0.81 and 0.86 MPa, and the catalyst performance is good.
[0098] Embodiment 19
[0099] The process and conditions are the same as those of Example 13. The difference from Example 13 is that the Ru18Pt12 / La-Al-RP-H1 catalyst prepared in Example 9 is loaded into the catalyst bed of the HAN liquid engine. The amounts of other materials and the operating conditions are the same as those of Example 13. From the test results, it can be seen that the HAN liquid propellant undergoes catalytic decomposition at room temperature. After 10,000 pulse tests, the catalyst bed temperature rises from room temperature to 268° C., the chamber pressure is stabilized between 0.80-0.86 MPa, and the catalyst performance is good.
[0100] Embodiment 20
[0101] The process and conditions are the same as those of Example 13. The difference in Example 13 is that the Ru22Pt8 / La-Al-RP-H1 catalyst prepared in Example 10 is loaded into the catalyst bed of the HAN liquid engine. The amounts of other materials and the operating conditions are the same as those of Example 13. From the test results, it can be seen that the HAN liquid propellant undergoes catalytic decomposition at room temperature. After 10,000 pulse tests, the catalyst bed temperature rises from room temperature to 270°C, the chamber pressure is stabilized between 0.81-0.86 MPa, and the catalyst performance is good.
[0102] Embodiment 21
[0103] The process and conditions are the same as those of Example 13. The difference from Example 13 is that the Ru25Pt10 / La-Al-RP-H1 catalyst prepared in Example 11 is loaded into the catalyst bed of the HAN liquid engine. The amounts of other materials and the operating conditions are the same as those of Example 13. From the test results, it can be seen that the HAN liquid propellant undergoes catalytic decomposition at room temperature. After 10,000 pulse tests, the catalyst bed temperature rises from room temperature to 274°C, the chamber pressure is stabilized between 0.81-0.87 MPa, and the catalyst performance is good.
[0104] Embodiment 22
[0105] The process and conditions are the same as those of Example 13. The difference in Example 13 is that the Ru20Pt15 / La-Al-RP-H1 catalyst prepared in Example 12 is loaded into the catalyst bed of the HAN liquid engine. The amounts of other materials and the operating conditions are the same as those of Example 13. From the test results, it can be seen that the HAN liquid propellant undergoes catalytic decomposition at room temperature. After 10,000 pulse tests, the catalyst bed temperature rises from room temperature to 269° C., the chamber pressure is stabilized between 0.81-0.86 MPa, and the catalyst performance is good.
[0106] Embodiment 23
[0107] The process and conditions are the same as those of Example 13. The difference from Example 13 is that the Ru15Pt15 / La-Al-RP-C catalyst prepared in Comparative Example 3 is loaded into the HAN liquid engine catalyst bed. The other material amounts and operating conditions are the same as those of Example 13. From the test results, it can be seen that the HAN liquid propellant has a slow catalytic decomposition reaction at room temperature, and the catalyst bed temperature rises slowly from room temperature to 90° C. When the 126th 40 pulses were performed, the chamber pressure was unstable and fluctuated between 0.09-0.45 MPa, and the 10,000 pulse test was not completed.
[0108] Embodiment 24
[0109] The process and conditions are the same as those of Example 13. The difference from Example 13 is that the Ru15Pt15 / La-Al-RP-N catalyst prepared in Comparative Example 4 is loaded into the HAN liquid engine catalyst bed. The other material amounts and operating conditions are the same as those of Example 13. From the test results, it can be seen that the HAN liquid propellant has a slow catalytic decomposition reaction at room temperature, and the catalyst bed temperature rises slowly from room temperature to 95°C. When the 130th 40 pulses were performed, the chamber pressure was unstable and fluctuated between 0.11-0.43Mpa, and the 10,000 pulse test was not completed.
[0110] Embodiment 25
[0111] The process and conditions are the same as those of Example 13. The difference from Example 13 is that the Ru15Pt15(imp) / La-Al-RP-H1 catalyst prepared in Comparative Example 5 is loaded into the HAN liquid engine catalyst bed. The other material dosages and operating conditions are the same as those of Example 13. From the test results, it can be seen that the HAN liquid propellant has a slow catalytic decomposition reaction at room temperature, and the catalyst bed temperature rises slowly from room temperature to 98°C. When the 150th 40 pulses were performed, the chamber pressure was unstable and fluctuated between 0.15-0.44Mpa, and the 10,000 pulse test was not completed.
[0112] Embodiment 26
[0113] The process and conditions are the same as those of Example 13. The difference from Example 13 is that the Ru25 / La-Al-RP-H1 catalyst prepared in Comparative Example 6 is loaded into the HAN liquid engine catalyst bed. The other material amounts and operating conditions are the same as those of Example 13. The pulse test results at room temperature are shown in FIG. Fig. 9 The results of the 100th 40 pulse test are shown in Fig.10 It can be seen from the figure that the HAN liquid propellant has a slow catalytic decomposition reaction at room temperature, and the catalyst bed temperature rises slowly from room temperature to 103°C. When the 180th 40 pulses were performed, the chamber pressure was unstable, fluctuating between 0.18-0.42Mpa, and the 10,000 pulse test was not completed.
[0114] Embodiment 27
[0115] The process and conditions are the same as those of Example 13. The difference from Example 13 is that the Pt20 / La-Al-RP-H1 catalyst prepared in Comparative Example 7 is loaded into the HAN liquid engine catalyst bed. The other material amounts and operating conditions are the same as those of Example 13. From the test results, it can be seen that the HAN liquid propellant has a slow catalytic decomposition reaction at room temperature, and the catalyst bed temperature rises slowly from room temperature to 85° C. When the 110th 40 pulses were performed, the chamber pressure was unstable and fluctuated between 0.12-0.45 MPa, and the 10,000 pulse test was not completed.
[0116] Embodiment 28
[0117] The process and conditions are the same as those of Example 13. The difference from Example 13 is that the Ru30Pt5 / La-Al-RP-H1 catalyst prepared in Comparative Example 8 is loaded into the HAN liquid engine catalyst bed. The other material amounts and operating conditions are the same as those of Example 13. From the test results, it can be seen that the HAN liquid propellant has a slow catalytic decomposition reaction at room temperature, and the catalyst bed temperature rises slowly from room temperature to 110° C. When the 200th 40 pulses were performed, the chamber pressure was unstable and fluctuated between 0.21-0.44 MPa, and the 10,000 pulse test was not completed.
[0118] Embodiment 29
[0119] The process and conditions are the same as those of Example 13. The difference from Example 13 is that the Ru10Pt25 / La-Al-RP-H1 catalyst prepared in Comparative Example 9 is loaded into the HAN liquid engine catalyst bed. The other material amounts and operating conditions are the same as those of Example 13. From the test results, it can be seen that the HAN liquid propellant has a slow catalytic decomposition reaction at room temperature, and the catalyst bed temperature rises slowly from room temperature to 123° C. When the 225th 40 pulses were performed, the chamber pressure was unstable and fluctuated between 0.22-0.42 MPa, and the 10,000 pulse test was not completed.
Claims
1. A method for preparing a highly dispersed ruthenium-platinum bimetallic catalyst, characterized in that: The catalyst comprises a catalyst carrier and active components Ru and Pt; the active component Ru accounts for 10-25wt% of the carrier mass, the Pt accounts for 5-20wt% of the carrier mass, and the active component metal particle size is 1.0-2.5nm; The catalyst carrier is RP type lanthanum aluminum oxide; the carrier has a layered structure with an interlayer spacing of 5-8nm; The catalyst carrier is prepared by a hydrothermal method, and the steps are as follows: First, at a molar ratio of La:Al=1:2~3:1, nitrate containing La and Al is dissolved in deionized water to obtain solution A, wherein the mass content of La nitrate is 2.5~6wt%; sodium hydroxide and sodium carbonate are dissolved in deionized water at a molar ratio of 2:3~3.5:1 to obtain solution B, wherein the molar ratio of sodium hydroxide to the sum of metal La and Al salt is 3:1~6:1; after mixing solutions A and B evenly, transfer them to a closed reactor, react at 100~120℃ for 10~20h, cool naturally to room temperature, wash and filter, dry at 80~100℃ for 10~20h, and calcine in air at 800~900℃ for 4~8h to obtain RP type lanthanum aluminum oxide; The preparation method of the highly dispersed ruthenium-platinum bimetallic catalyst comprises the following steps: 1) First, a microemulsion containing Ru and Pt is prepared, and an active metal Ru precursor and a chloroplatinic acid microemulsion, hexadecyltrimethylammonium bromide and n-hexane are prepared in a mass ratio of 1.6-2.5:2.7-3.6:4.5-5.5 to prepare a microemulsion solution containing active metals Ru and Pt, wherein the mass content of the active metal Ru precursor in the solution is 2.5-7wt%, and the mass content of chloroplatinic acid is 1-5wt%; 2) Spray a microemulsion solution of a soluble salt of active metal Ru with a content of 1.0-2.5 wt% relative to the carrier and 0.5-2.0 wt% chloroplatinic acid with a content of 0.5-2.0 wt% relative to the carrier onto lanthanum aluminum oxide, let it stand for 1-2 hours, freeze-dry it at a low temperature of -25--15°C for 8-12 hours, and then calcine it at 300-400°C for 2-4 hours in an inert atmosphere to obtain a catalyst in which active metals Ru and Pt are dispersed between the layers and on the surface of lanthanum aluminum oxide; 3) Repeat steps 1) and 2) 8-10 times, and perform steps 1) and 2) 9-11 times in total; The soluble salt of the active metal Ru is one or both of ruthenium acetate and ruthenium trichloride solution.
2. A highly dispersed ruthenium-platinum bimetallic catalyst prepared by the method for preparing a highly dispersed ruthenium-platinum bimetallic catalyst according to claim 1.
3. The use of the highly dispersed ruthenium-platinum bimetallic catalyst as claimed in claim 2, characterized in that: The highly dispersed ruthenium-platinum bimetallic catalyst is used for catalyzing the decomposition of HAN propellant.
4. The use of the highly dispersed ruthenium-platinum bimetallic catalyst as claimed in claim 3, characterized in that: The highly dispersed ruthenium-platinum bimetallic catalyst is used to catalyze the rapid start-up and decomposition of HAN propellant at room temperature, meeting the long-life application requirements of HAN propellant with tens of thousands of pulse starts.
5. The use of the highly dispersed ruthenium-platinum bimetallic catalyst as claimed in claim 3 or 4, characterized in that: The catalyst needs to be activated before the catalytic reaction, and the pretreatment conditions are: reduction at 400-600° C. for 2-4 hours in a hydrogen atmosphere.
Citation Information
Patent Citations
Supports and catalysts comprising rare earth aluminates, and their use in partial oxidation
US20050265920A1